Quality Evaluation of Refrigerated Salted Butter Made with Goat and Cow Milk - Pradana, Mahendra Wahyu Eka; Murti, Tridjoko Wisnu (Buletin Peternakan, 2024)
Butter is a dairy product that is susceptible to oxidation, which causes a rancid taste and a short shelf life. The quality of the butter depends on the quality of milk. The aim of the study is to determine the quality of butter made from goat and cow reared by small-scale farmers in Yogyakarta with the traditional manufacturing process. The milk of Saanen-Peranakan Ettawa (Sapera)  goats and Fresian Holstein were taken from farmers in Sleman district, Yogyakarta, Indonesia. Butters were sampled after 0, 15, 30 days storage. This study used the Nested Design method , namely the nested quality of butter in the type of milk. The result showed that butter made from cow milk produced a higher fat content compared to goat milk butter (P<0.05), namely 85.29 ± 0.04% and 80.10 ± 0.27%. The acid value increased while pH value was decreased during storage (P<0.05). There was no increase in peroxide value in cow butter but there was an increase in goat butter on day 0 to day 15 (P<0.05). It can be concluded that the goat and cow milk reared by small-scale farmers in Yogyakarta have good quality so it produced good quality butter which is still good for consumption until 30 days of storage in the refrigerator.